PERAN GURU DALAM MENUMBUHKAN MINAT SISWA TERHADAP BAHASA JAWA DI KELAS III SD - Ana Zumrotul Isnaini; Mia Adhinda Putri; Alfaiza Sabrina; Irsyanda Naufal Faiza; Himathul Aulia Farikha; Ali Ismunadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the role of teachers in fostering students' interest in learning Javanese in class III SDN Purwoyoso 02. This study uses a qualitative approach with a case study type, involving one teacher and 21 students. Data were collected through observation, interviews, and questionnaires. The results of the study indicate that teachers apply various innovative learning strategies, such as PjBL, storytelling, group discussions, and role simulations, as well as utilizing audio-visual media. This approach creates a more lively and contextual learning atmosphere, thereby increasing student involvement and interest. Teachers also take a personal approach according to student characteristics. Based on the questionnaire, most students showed enthusiasm and relevance to learning Javanese. This finding confirms the importance of the role of teachers in fostering interest in learning through varied and relevant strategies.